2013
DOI: 10.22146/ijc.21280
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Biomaterials Film Based on Poly(vinyl Alcohol) and Fish Scale Collagen by Repetitive Freeze-Thaw Cycles Followed by Gamma Irradiation

Abstract: The polymeric biomaterial film based on poly (vinyl alcohol) (PVA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Also resonances at 1341 cm − 1 and 861 cm − 1 assigned for amide III, C-N and N–H functionalities and for amide V respectively. 9,33,36…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also resonances at 1341 cm − 1 and 861 cm − 1 assigned for amide III, C-N and N–H functionalities and for amide V respectively. 9,33,36…”
Section: Resultsmentioning
confidence: 99%
“…The fabricated PVA-Tyr/Col fibrous exhibited characteristic bands of PVA-Tyr and Col (Figure 3(b)). [33][34][35] The peaks of PVA-Tyr demonstrated by the peaks 3435 cm À1 indicates the presence of O-H group with polymeric association and N-H stretching of secondary amide and peaks at 2932 cm À1 and 2872 cm À1 related to asymmetric and symmetric CH 2 stretching respectively. It also shows a peak at 1634 cm À1 carbonyl stretching, 1248 cm À1 C-O and C-C stretching, 1102 cm À1 symmetric C-O-C stretching.…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The PVA/collagen blend gave a strong -O–H stretching band, very weak amide I and II band and the shift of −O-Hstretch to a lower position from 3304 to 3280 cm –1 indicated that the occurrence of cross-linking between hydroxyl groups of PVA with the amide group of collagen might be through a hydrogen bond. 10 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…By blending collagen with PVA, weak properties of collagen such as poor mechanical strength and fast biodegradation rate could be overwhelmed. 10 The pigment responsible for tanning of the skin is melanin, though it helps in protecting the skin from UV-induced DNA degradation, the abnormal accumulation of melanin due to higher tyrosinase activity results in uneven patches on the skin causing an aesthetic problem. Therefore, natural tyrosinase inhibitor curcumin is one of the choices as a skincare ingredient in cosmetic products.…”
Section: Introductionmentioning
confidence: 99%